Healthy Academic Processes in the University Context - Ileana Castillo-Cedeño; Luz Emilia Flores-Davis; Giselle Miranda-Cervantes (Universidad Nacional, Costa Rica, 2015)
This scientific article aims to identify the perceptions of healthy academic administrative processes in the university context. This contribution was directed by socio-educational research processes generated at the National University of Costa Rica (UNA), in the Center for Research and Teaching in Education (CIDE). The issue of health is part of the institutional plan and the Center. Whereas health, like education, is a fundamental human right that deserves responsibilities from pedagogy as educational science research, which analyzes and transforms. Therefore, it is urgent, in the face of new global challenges to address planetary crises linked to health. This research is based on the naturalistic paradigm and a methodology that assumes a type of joint research, where using a semi-structured interview achieves a deeper analysis that allows contrasting perceptions, theories and practices by comparing qualitative and quantitative data. From the results of impact the concept of Healthy Pedagogy is unknown in the university context. The connection between education and health as a holistic theoretical, epistemological and axiological construction, it includes the complexity theory that allows the university to take challenges with an enormous potential; promoting environments, styles and healthy organizations from healthy academic administrations from both individual and collective aspects. It is possible to construct new sense of orders, which assume in a responsible manner to re-dignify the university life in its various spaces and dimensions. Research has the valuable potential to become a dynamic element of institutional policies in favor of life.